2016
DOI: 10.1016/j.fertnstert.2016.07.224
|View full text |Cite
|
Sign up to set email alerts
|

Special research presentation: vitamin d reverses the adverse effects of advanced glycation end products on granulosa cells

Abstract: ANOVA) of the degree and distribution of 116 morphological assessments from 10 tissues from 10 rats from 4 TRTS are nearing completion; preliminarily no toxic TRT effects exist.CONCLUSIONS: Biologically significant increases in any of 4 manifestations of toxicity (death, structural abnormalities, growth alterations, and functional deficits) are indicative of an agent's toxicity. This is the first preclinical evidence showing TRT with rTIMP1+Ab that restores ovulatory function in endometriosis does not cause to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In that study, the human luteinized granulosa cells were treated with exogenous AGEs in vitro and showed significant increase in LHR and AMHR-II mRNA levels, but had no change in AMH mRNA expression levels. Compared to luteinized granulosa cells treated without exogenous AGEs in vitro, those treated with exogenous AGEs had significant increase in CYP11A1, 3β-HSD, StAR, and CYP17A1 mRNA expression levels as well as a significant secretion of estradiol [ 79 ]. These findings suggest that there is a relationship between exogenous AGEs and steroid expression.…”
Section: Ovarian Dysfunctionmentioning
confidence: 99%
“…In that study, the human luteinized granulosa cells were treated with exogenous AGEs in vitro and showed significant increase in LHR and AMHR-II mRNA levels, but had no change in AMH mRNA expression levels. Compared to luteinized granulosa cells treated without exogenous AGEs in vitro, those treated with exogenous AGEs had significant increase in CYP11A1, 3β-HSD, StAR, and CYP17A1 mRNA expression levels as well as a significant secretion of estradiol [ 79 ]. These findings suggest that there is a relationship between exogenous AGEs and steroid expression.…”
Section: Ovarian Dysfunctionmentioning
confidence: 99%
“…sRAGE levels in follicular fluid are reduced in PCOS women [ 93 ]. It has been observed that vitamin D supplementation in PCOS women may improve the steroidogenesis and enzymatic antioxidant activity in the human GC [ 94 ] and it may attenuate the actions of AGEs [ 95 , 96 ]. AGEs play a role in age-related bone loss [ 97 , 98 ].…”
Section: Vitamin D and Pcosmentioning
confidence: 99%